1995
DOI: 10.1523/jneurosci.15-02-01605.1995
|View full text |Cite
|
Sign up to set email alerts
|

The neurophysiology of figure-ground segregation in primary visual cortex

Abstract: The activity of neurons in the primary visual cortex of the awake macaque monkey was recorded while the animals were viewing full screen arrays of either oriented line segments or moving random dots. A square patch of the screen was made to perceptually pop out as a circumscribed figure by virtue of differences between the orientation or the direction of motion of the texture elements within that patch and the surround. The animals were trained to identify the figure patches by making saccadic eye movements to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

88
711
15
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 842 publications
(819 citation statements)
references
References 21 publications
88
711
15
5
Order By: Relevance
“…These different schemes may explain the 490 opposing power changes in gamma reported here. While opposing power changes in 491 gamma within the same visual area have not been reported before, we note that previous 492 studies on figure-ground segregation have reported either increases (Lamme, 1995; 493…”
mentioning
confidence: 43%
See 2 more Smart Citations
“…These different schemes may explain the 490 opposing power changes in gamma reported here. While opposing power changes in 491 gamma within the same visual area have not been reported before, we note that previous 492 studies on figure-ground segregation have reported either increases (Lamme, 1995; 493…”
mentioning
confidence: 43%
“…The role of gamma rhythms in figure-ground segregation is hypothesised to result from 486 one or two general processes: (i) region labelling, achieved by labelling corresponding 487 elements in an isomorphic surface representation (Lamme, 1995); and/or (ii) border 488 ownership coding, achieved through contour representation following the activity of 489 orientation-selective units (Craft, et al, 2007). These different schemes may explain the 490 opposing power changes in gamma reported here.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The essence of Wgure/ ground organization is to assign an increased salience to the Wgure relative to the ground regions. In contrast to neurophysiological studies (e.g., Lamme 1995), to date no fMRI study has reported a response that is retinotopically matched with an arbitrary Wgure shape, in the absence of diVerentiating local cues.…”
Section: Experiments 1: Figure-ground Conwgurationmentioning
confidence: 66%
“…In terms of neural architecture, does the mechanism employ lateral interactions (e.g., Gerrits and Vendrik 1970;Grossberg and Mingolla 1985;Grossberg 1994;Baek and Sajda 2005;Pao et al 1999;Zhaoping 2005), top-down feedback (e.g., Lamme and Roelfsema 2000;Lamme et al 2002;Roelfsema et al 2002;Craft et al 2007) or more sophisticated combinations? In terms of its coding mechanism, do the Wgure/ground conWgurations use border-based coding (e.g., von der Heydt et al 2003Heydt et al , 2005Craft et al 2007) or region-based coding (e.g., Lamme 1995;Zipser et al 1996;Lamme et al 1998;Super et al 2001;Roelfsema et al 2002)?…”
Section: Introductionmentioning
confidence: 99%